Synergic effect between TRAIL gene and curcumin in magnetic chitosan nanoparticles on cancer cells apoptosis enhanced by laser photoactivation - Alvizo Báez, Cynthia Aracely; Peña Torres, Arnulfo Aramis; Terrazas Armendáriz, Luis Daniel; Luna Cruz, Itza Eloísa; Uscanga Palomeque, Ashanti Concepción; Sampayo Reyes, Adriana; Tamez Guerra, Reyes Silvestre; Rodríguez Padilla, Cristina; Alcocer González, Juan Manuel (Springer Nature, 2022)
The Apoptosis is an intensely studied mechanism for cancer therapy. Various genes, drugs, and molecules have been combined to potentiate the apoptotic effect against tumor cells. Magnetic nanocomplexes with biopolymers have been proposed as nanocarriers for delivery of active molecules and improve apoptosis induction. To these purpose were formulated magnetic nanoparticles with curcumin coated chitosan (MNPs-CHI-TPP-CUR) and magnetic nanoparticles with pCEM-TRAIL plasmid coated chitosan (MNPsCHI-TPP-TRAIL) for use alone or in combination to induce the apoptosis of B16F10 tumor cells because curcumin is capable of overexpressing receptors TRAIL required for apoptosis induction. Also, curcumin (CUR) has been used as a photosensitizer in photodynamic therapy (PDT). In this work, it was produced and characterized nanoparticles with curcumin and nanoparticles with TRAIL gene. Both types of nanoparticles were~200 nm size. The results showed that the combination of (MNPs-CHI-TPP-CUR) and (MNPsCHI-TPP-TRAIL) induced a significant increase in cellular death within 48 h compared with the effect of each nanocomplex individually, demonstrating a synergic effect. This is the first description the synergic interaction between TRAIL gene and curcumin drug to improve the apoptosis in cancer cells. Also, it was determined that cellular death was potentiated when the treated cells were exposed to laser photoactivation with wavelengths of 405 nm and 532 nm for 15 min.